Pelayanan Prima Dalam Pembuatan Akta Kelahiran Di Dinas Kependudukan Dan Catatan Sipil Kabupaten Kolaka - fitri, ade; Djabbar, Isra; Mardiana, Mardiana; Hidayat, Rahmat (Jurnal Ilmu Pemerintahan, 2025)
This study aims to measure and analyze the Excellent Service (Pelayanan Prima) in the Issuance of Birth Certificates at the Kolaka Regency Population and Civil Registration Office (Disdukcapil). The research is grounded in the six competencies of excellent service proposed by Priansa (2017): Ability, Attitude, Appearance, Attention, Action, and Accountability. The study employed a descriptive qualitative approach and was located at the Disdukcapil Kolaka. Primary data were collected through in-depth interviews with six informants, including service staff and community members, and field observation, supported by secondary data from literature and documentation (Ade Fitri, 2025). Data analysis utilized the descriptive qualitative technique involving data reduction, data display, and conclusion drawing/verification (Sugiyono, 2017). Findings indicate that overall service implementation is good, particularly in Accountability and Action, with documents processed quickly (3 days, faster than the 5-day target) and confirmed as free of charge. However, service quality is hindered by three main issues : 1) Ability: Shortage of human resources and low public awareness of procedures, leading to incomplete application files; 2) Attitude/Appearance: Staff occasionally display a less focused or indifferent attitude (cuek) during interactions, as reported by applicants, and struggle to manage the unreliable SIAK (Population Information System) due to unstable network connectivity ; and 3) Action: System errors force manual procedures, causing delays not compliant with the Standard Operating Procedure (SOP). The research confirms that these non-optimal competencies inhibit the full realization of Excellent Service. Research Implications: The study highlights the need for a focused effort by Disdukcapil Kolaka to enhance staff technical skills in handling the SIAK system and to improve the non-physical aspects of staff conduct, such as focusing on professionalism and customer-facing communication. Originality/Value: This research is critical as it offers a specific diagnostic assessment of the quality of birth certificate issuance in Kolaka using the comprehensive Priansa (2017) competency model, filling a gap in the literature regarding local public administration performance.